2015
DOI: 10.1016/j.jtbi.2015.04.038
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical model of the endothelial cell morphology due to different waveforms

Abstract: Endothelial cells are key units in the regulatory biological process of blood vessels. They represent an interface to transmit variations on the fluid dynamic changes. They are able to adapt its cytoskeleton, by means of microtubules reorientation and F-actin reorganization, due to new mechanical environments. Moreover, they are responsible for initiate a huge cascade of biological processes, such as the release of endothelins (ET-1), in charge of the constriction of the vessel and growth factors such as TGF −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…As previously mentioned, Sáez et al 26 presented the 3D remodelling of endothelial cells as the combined effect of OSI and TAWSS in a computational framework, which fitted experimental works presented before in in vitro studies.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…As previously mentioned, Sáez et al 26 presented the 3D remodelling of endothelial cells as the combined effect of OSI and TAWSS in a computational framework, which fitted experimental works presented before in in vitro studies.…”
Section: Methodsmentioning
confidence: 89%
“…However, as previously mentioned, recent work shows that ECSI can be affected by other indices as well , such as OSI. Based on the seminal paper by Levesque et al, 25 a more recent work from Sáez et al 26 presented how a combination of OSI and TAWSS modifies the endothelial cell shape. This relationship will be the key for the modelling work presented here.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies (Malek et al, 1999 ; Xiang et al, 2010 ; Chiu and Chien, 2011 ; Meng et al, 2014 ) have shown that regions with low average shear stress combined with highly oscillatory shear stress have increased endothelial permeability along with other pathological responses. More recently, Sáez et al ( 2015 ) presented the 3D remodeling of endothelial cells as the combined effect of OSI and TAWSS in a computational framework, which fitted experimental works presented before in in vitro studies.…”
Section: Methodsmentioning
confidence: 91%
“…However, as previously mentioned, recent work shows that ECSI can be affected by other indices as well , such as OSI. Based on the seminal paper by Levesque et al ( 1986 ), excellent work from Sáez et al ( 2015 ), presents how different OSI and TAWSS modify the endothelial cell shape. This combined relationship will be key for the modeling work presented here.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation